Reconfiguring health knowledges? Contemporary modes of self-care as ‘everyday fringe medicine’ - Vuolanto Pia; Harley Bergroth; Johanna Nurmi; Suvi Salmenniemi (SAGE Publications, 2022)
The contestation of expertise is perhaps nowhere more pronounced than in the field of health and well-being, on which this article focuses. A multitude of practices and communities that stand in contentious relationships with established forms of medical expertise and promote personalised modes of self-care have proliferated across Euro-American societies. Drawing on multi-sited ethnography in three domains – body–mind–spirit therapies, vaccine hesitancy and consumer-grade digital self-tracking – we map such practices through the concept of ‘everyday fringe medicine’. The concept of everyday fringe medicine enables us to bring together various critical health and well-being practices and to unravel the complex modes of contestation and appreciation of the medical establishment that are articulated within them. We find three critiques of the medical establishment – critiques of medical knowledge production, professional practices and the knowledge base – which make visible the complexities related to public understandings of science within everyday fringe medicine.